Analysis of content of heavy metals in soil and mosses, the surroundings of kurchatov town (Eurasian Journal of Ecology, 2016)
This article discusses the contents of heavy metals on the example of the three most common types of moss: Brachythecium rivulare, Fontinalis antipyretica, Cratoneurum filicinum. Contains data on the content ofheavy metals in the soil of the explored territory where the samples were gathered moss. Also the article contains comparative data on maximum permissible concentrations of heavy metals in the world (on the example of several countries) and medial values of the content of heavy metals in mosses in the surveyed territory and other countries.
Keywords: mosses; heavy metals; maximum allowable concentration; medial values